Evaluation of patients with thyrotoxic autoimmune thyroiditis by color flow doppler ultrasonography. Issue 1 (2013) - Karakaş, Ömer; Karakaş, Ekrem; Çullu, Neşat; Demir, Yusuf; Küçükyavaş, Yasin; Sürücü, Erdem; Yener, Serkan; İğci, Enis
No abstract available